WESSELS, JB Inventory of documents - WESSELS, JB (ARCA, 2018)
Single group photograph of Maree Kohler, Jannie Wessels, ADCJ Jacobsz, ADC Land, JHB Wessels, Comdt Louis Notha, Genl Wessels, Comdt FP Jacobsz, Comdt HJ Bruwers
COVERAGE: 0.01 metres
Keywords: WESSELS, JB